P62 Thoroplastic Reconstruction Following Chest Wall Resection. (14th November 2013) - Lai, A; Jones, M; Duff, C
Abstract : Background: Reconstructive procedures following chest wall resection continue to improve. This study reviews our experience of chest wall reconstruction with multidisciplinary approach. Methods: We conducted a retrospective review of 25 patients who underwent chest wall reconstruction in our department between September 2006 and April 2013. Results: 13 cases were primary chest wall tumours. Underlying diseases included chondrosarcoma, osteosarcoma, sarcomas, primary and metastatic lung tumours, radionecrosis and Aspergilloma. Mean number of ribs resected was 3.5. Reconstruction was performed using Marlex mesh with methyl methacrylate in all patients. The exact nature of the resectional defect cannot be fully planned for reconstruction until after its creation. Muscle, myocutaneous and chimeric flaps were used. Soft tissue reconstruction was carried out using Latissimus Dorsi muscle or myocutaneous flaps in 10 patients, Pectoralis Major in 2 patients, Rectus Abdominis in 1 patient, Trapezius in 1 patients and Serratus Anterior in 1 patient. 3 patients had post-operative complications requiring re-admission. There were no cases of 30-day mortality on follow-up. Conclusions: Chest wall resection and reconstruction with Marlex mesh had excellent results, and is useful for managing defects following chest wall resectionwith low morbidity. The importance of close collaboration between reconstructive and cardiothoracic surgery team is demonstrated.